Ambulatory detection of sleep apnea using a non‐contact biomotion sensor. (30th June 2019) - Crinion, Sophie J.; Tiron, Roxana; Lyon, Graeme; Zaffaroni, Alberto; Kilroy, Hannah; Doheny, Emer; O'Hare, Emer; Boyle, Patricia; Russell, Audrey; Traynor, Mark; Kent, Brian D.; Ryan, Silke; et al.
Summary: The high prevalence of obstructive sleep apnea has led to increasing interest in ambulatory diagnosis. The SleepMinder™ (SM) is a novel non‐contact device that employs radiofrequency wave technology to assess the breathing pattern, and thereby estimate obstructive sleep apnea severity. We assessed the performance of SleepMinder™ in the home diagnosis of obstructive sleep apnea. One‐hundred and twenty‐two subjects were prospectively recruited in two protocols, one from an unselected sleep clinic cohort ( n  = 67, mean age 51 years) and a second from a hypertension clinic cohort ( n  = 55, mean age 58 years). All underwent 7 consecutive nights of home monitoring (SMHOME ) with the SleepMinder™ as well as inpatient‐attended polysomnography in the sleep clinic cohort or cardiorespiratory polygraphy in the hypertension clinic cohort with simultaneous SleepMinder™ recordings (SMLAB ). In the sleep clinic cohort, median SMHOME apnea–hypopnea index correlated significantly with polysomnography apnea–hypopnea index ( r  = .68; p  < .001), and in the hypertension clinic cohort with polygraphy apnea–hypopnea index ( r  = .7; p  < .001). The median SMHOME performance against polysomnography in the sleep clinic cohort showed a sensitivity and specificity of 72% and 94% for apnea–hypopnea index ≥ 15. Device performance was inferior in females. In the hypertension clinic cohort, SMHOME showed a 50% sensitivity and 72% specificity for apnea–hypopnea index ≥ 15. SleepMinder™ classified 92% of cases correctly or within one severity class of the polygraphy classification. Night‐to‐night variability in home testing was relatively high, especially at lower apnea–hypopnea index levels. We conclude that the SleepMinder™ device provides a useful ambulatory screening tool, especially in a population suspected of obstructive sleep apnea, and is most accurate in moderate–severe obstructive sleep apnea.